Experimental study of premixed hydrogen enriched natural gas under an alternating-current (AC) electric field and application of support vector machine (SVM) on electric field assisted combustion. (15th December 2019) - Duan, Hao; Li, Zhijie; Wang, Bo; Mehra, Roopesh Kumar; Luo, Sijie; Xu, Chuanguo; Sun, Baigang; Wang, Xi; Ma, Fanhua
Highlights: Applying electric field can improve the flame propagation and enhance the combustion of HCNG fuel. The promotion effect of electric field on the propagation of HCNG flame decreases as the hydrogen blend ratio increases. The enhancement effect of electric field on the combustion of HCNG fuel decreases as the hydrogen blend ratio increases. Adding electric field can improve the combustion of lean burn conditions effectively. SVM method can predict the flame propagation and combustion properties under an electric field effectively. Abstract: Present research study explores the flame propagation and combustion characteristics of premixed hydrogen enriched natural gas under a 100 Hz low-frequency alternating-current (AC) electric field with various hydrogen blend ratios (0–100%) and fuel–air equivalent ratios (1.0/0.8/0.6) in a constant volume combustion chamber. Results show that: (1) With the application of the electric field, although the maximum pressure increases slightly, the mean flame propagation speed increases and the initial/main duration shortens apparently. At a hydrogen blend ratio of 20% and an equivalent ratio of 0.8, the mean flame propagation speed increases by 10.06%, and the initial/main duration shortens by 13.46%/10.72%. (2) The promotion effect of the electric field on the flame propagation and combustion of the fuel decreases gradually as the hydrogen blend ratio increases. There exists a maximum value of hydrogen blend ratio that electric field makes no difference to the combustion process and the value increases with the excess air ratio. The electric field almost has no effect on the pure hydrogen fuel. (3) Adding the AC electric field can improve the combustion of lean burn conditions more effectively than that of higher equivalent ratio conditions. Meanwhile, the support vector machine is applied for the predication of the flame propagation and combustion characteristics under electric fields. The prediction performance of the optimal model obtained by the SVM method for the maximum pressure is very accurate, while that of the mean flame propagation speed is relatively limited.